Proceedings of the 53rd Annual Meeting of the Association for Computational Linguistics and the 7th International Joint Confere 2015
DOI: 10.3115/v1/p15-2058
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Clustering and Convolutional Neural Network for Short Text Categorization

Abstract: Short texts usually encounter data sparsity and ambiguity problems in representations for their lack of context. In this paper, we propose a novel method to model short texts based on semantic clustering and convolutional neural network. Particularly, we first discover semantic cliques in embedding spaces by a fast clustering algorithm. Then, multi-scale semantic units are detected under the supervision of semantic cliques, which introduce useful external knowledge for short texts. These meaningful semantic un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(81 citation statements)
references
References 15 publications
0
78
0
3
Order By: Relevance
“…Another application uses Recurrent Neural Networks for question answering systems about paragraphs [15], and a Neural Responding Machine (NRM) has been proposed for a Short-Text Conversation generator, which is based on neural networks [21]. In addition, Recurrent Neural Networks models offered state-of-the-art performance for sentiment classification [13], target-dependent sentiment classification [25] and question answering [15]. Adaptive Recurrent Neural Network (AdaRNN) is introduced for sentiment classification in Twitter promotions based on the context and syntactic relationships between words [2].…”
Section: Recurrent Neural Network Approachesmentioning
confidence: 99%
“…Another application uses Recurrent Neural Networks for question answering systems about paragraphs [15], and a Neural Responding Machine (NRM) has been proposed for a Short-Text Conversation generator, which is based on neural networks [21]. In addition, Recurrent Neural Networks models offered state-of-the-art performance for sentiment classification [13], target-dependent sentiment classification [25] and question answering [15]. Adaptive Recurrent Neural Network (AdaRNN) is introduced for sentiment classification in Twitter promotions based on the context and syntactic relationships between words [2].…”
Section: Recurrent Neural Network Approachesmentioning
confidence: 99%
“…The research discussed in this paper applied a simple CNN architecture that demonstrated successful results in various domains (Kim, 2014). Many variants on this architecture were proposed (Johnson and Zhang, 2014;Chen et al, 2015;Ma et al, 2015;Nguyen and Grishman, 2015;Wang et al, 2015;Chen and Ku, 2016;Laha and Raykar, 2016). It is conceivable that one of these variants may achieve better results for detecting indications of fraud in texts.…”
Section: Discussionmentioning
confidence: 99%
“…Both Ma et al (2015) and Zhang et al (2016b) reported an accuracy of 95.6%. Wang et al (2015) achieved the highest accuracy, 97.2%, with GloVe word embeddings.…”
Section: Topic and Question Classificationmentioning
confidence: 99%
See 2 more Smart Citations